2021
DOI: 10.1038/s41598-020-80776-2
|View full text |Cite
|
Sign up to set email alerts
|

Differential relationships of PTSD symptom clusters with cortical thickness and grey matter volumes among women with PTSD

Abstract: Structural neuroimaging studies of posttraumatic stress disorder (PTSD) have typically reported reduced cortical thickness (CT) and gray matter volume (GMV) in subcortical structures and networks involved in memory retrieval, emotional processing and regulation, and fear acquisition and extinction. Although PTSD is more common in women, and interpersonal violence (IPV) exposure is a more potent risk factor for developing PTSD relative to other forms of trauma, most of the existing literature examined combat-ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 81 publications
1
27
0
Order By: Relevance
“…Starting with emerging adults (15-20 years and 20-30 years) and other age groups, we saw multiple nodes having centrality differences in all brain lobes with heavy conglomeration in the occipital regions. This advocates for disrupted frontolimbic circuitry in pediatric PTSD, consistent with previous studies (Herringa, 2017) and disproportionately heavy occipital involvement in adult PTSD (Chao, Lenoci, & Neylan, 2012; Crombie et al, 2021).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Starting with emerging adults (15-20 years and 20-30 years) and other age groups, we saw multiple nodes having centrality differences in all brain lobes with heavy conglomeration in the occipital regions. This advocates for disrupted frontolimbic circuitry in pediatric PTSD, consistent with previous studies (Herringa, 2017) and disproportionately heavy occipital involvement in adult PTSD (Chao, Lenoci, & Neylan, 2012; Crombie et al, 2021).…”
Section: Discussionsupporting
confidence: 87%
“…By contrast, female subjects with PTSD showed higher centrality than female controls in bilateral frontal and temporal lobes, including the bilateral insula. Areas like the vmPFC (Kuhn & Gallinat, 2013), anterior cingulate (Clausen et al, 2020) and superior occipital gyrus (Crombie, Ross, Letkiewicz, Sartin-Tarm, & Cisler, 2021) have been implicated in pathophysiology of PTSD. However, they have not shown sex differences in previous studies but showed differences in our SCN analyses.…”
Section: Discussionmentioning
confidence: 99%
“…All study procedures were approved by the respective Institutional Review Boards at UAMS and UW. Inclusion criteria consisted of female sex, age 21–50 years, and current diagnosis of PTSD related to assaultive violence exposure ( Crombie et al, 2021c ). PTSD diagnosis and symptom severity was assessed using the Clinician Administered PTSD Scale for DSM-5 (CAPS-5; ( Weathers et al, 2013 , Weathers et al, 2018 )).…”
Section: Methodsmentioning
confidence: 99%
“…Most recently, in the current COVID19 pandemic, millions of people worldwide have been suffering from PTSD disease (Pfefferbaum & North, 2020). Psychologically and epigenetically, women are more susceptible to PTSD than men (Christiansen & Berke, 2020; Crombie et al, 2021). Additionally, the children also have a high rate of PTSD (Dutheil et al, 2021; Rehman et al, 2020).…”
Section: Introductionmentioning
confidence: 99%